PENGARUH KREDIBILITAS MEREK TERHADAP NIAT BELI DENGAN MEDIASI KUALITAS YANG DIRASA KONSUMEN PRODUK BATIK JETIS DI SIDOARJO - Banu Caesar Firmansyah; Emma Julianti (STIE Perbanas Surabaya, 2014)
The purpose of this study is to examine the effect of brand credibility on the purchase intentionmediated by consumers perceived quality of batik Jetis in Sidoarjo. This research wasconducted in Sidoarjo communities who have seen batik Jetis Sidoarjo. The data used wereprimary data obtained directly from respondents by using questionnaire. The respondentswere batik Jetiss consumers. Samples used were selected through judgment sampling techniques.One hundred forty five questionnaires were distributed to the respondents. One hundredand ten data was analyzed using SEM and processed using software AMOS 21. The resultsshowed that brand credibility has a significant influence on customers perceived quality.While customers perceived quality has no significant effect on the purchase intention.Likewise, brand credibility has no significant influence on customers purchase intention.Based on these results we can conclude that customers perceived quality does not mediatethe relationship between the credibility of the brand with the customers purchase intention.